P–431 Human oocytes in-vitro maturation efficacy from infancy to adulthood – is there an optimal age?. (6th August 2021) - Karavani, G; Wasserzug-Pash, P; Mordechai-Daniel, T; Klutstein, M; Imbar, T
Abstract: Study question: Does human oocytes in-vitro maturation (IVM) effectiveness change throughout childhood, adolescence and adulthood in girls and women undergoing fertility preservation via ovarian tissue cryopreservation (OTC) prior to chemo-radiotherapy exposure? Summary answer: The optimal age for IVM is from menarche to 25 years, while pre-menarche girls and women older than 30 years have extremely low maturation rates. What is known already: In vitro maturation of oocytes from antral follicles seen during tissue harvesting is a fertility preservation technique with potential advantages over OTC, as mature frozen and later thawed oocyte used for fertilization poses decreased risk of malignant cells re-seeding, as compared to ovarian tissue implantation. We previously demonstrated that IVM performed following OTC in fertility preservation patients, even in pre-menarche girls, yields a fair amount of oocytes available for IVM and freezing for future use. Study design, size, duration: A retrospective cohort study, evaluating IVM outcomes in chemotherapy naïve patients referred for fertility preservation by OTC that had oocyte collected from the medium with attempted IVM between 2003 and 2020 in a university affiliated tertiary center. Participants/materials, setting, methods: A total of 133 chemotherapy naïve patients aged 1–35 years with attempted IVM were included in the study. The primary outcome was IVM rate in the different age groups – pre-menarche (1–5 years and ≥6 years), post-menarche (menarche–17 years), young adults (18–24 years) and adults (25–29 and 30–35 years). Comparison between paired groups for significant difference in the IVM rate parameter was done using the Tukey's Studentized Range (HSD) Test. Main results and the role of chance: A gradual increase in mean IVM rate was demonstrated in the age groups over 1 to 25 years (4.6% (1–5 years), 23.8% (6 years to menarche) and 28.4% (menarche to 17 years), with a peak of 38.3% in the 18–24 years group, followed by a decrease in the 25–29 years group (19.3%), down to a very low IVM rate (8.9%) in the 30–35 years group. A significant difference in IVM rates was noted between the age extremes – the very young (1–5 years) and the oldest (30–35 years) groups, as compared with the 18–24-year group (p < 0.001). Number of oocytes matured, percent of patients with matured oocytes and overall maturation rate differed significantly (p < 0.001). Limitations, reasons for caution: Data regarding ovarian reserve evaluation was not available for most of the patients, due to our pre-op OTC procedures protocol. None of our patients have used their frozen in-vitro matured oocytes, as such further implications of age on in-vitro matured oocytes quality and implantation potential has yet to be evaluated. Wider implications of the findings: Our finding of extremely low success rates in those very young (under 6 years) and older (≥30 years) patients suggest that IVM of oocyte retrieved during OTC prior to chemotherapy should not be attempted in these age group. Trial registration number: N/A